Advances and challenges of nanostructured electrodes for Li–Se batteries. Issue 21 (15th May 2017) - Jin, Jun; Tian, Xiaocong; Srikanth, Narasimalu; Kong, Ling Bing; Zhou, Kun
Abstract : In this review, the recent advances of nanostructured electrodes for lithium–selenium batteries and their characterizations and mechanisms are reviewed and discussed. Abstract : As an alternative to the energy storage system of lithium–sulfur (Li–S) batteries, the lithium–selenium (Li–Se) battery system has attracted much attention due to its high-energy (power) density, high theoretical capacity, good cycle performance, excellent rate performance, moderate output voltage, low cost and environmental benignity. However, the application of Li–Se batteries is hindered by various challenges including low loading and utilization of active materials, low coulombic efficiency, capacity fading, poor electrical conductivity and shuttling of polyselenide intermediates. In order to overcome these shortcomings and enhance the electrochemical performance, many efforts have been made in recent years including employing micro/nanostructured carbon materials/Se, transition metal oxide/Se, Se compounds, Se alloys or fully lithiated Li2 Se as electrodes and functional interlayer adsorbents and electrolyte additives. Herein, the recent advances of nanostructured electrodes for Li–Se batteries and their characterizations and mechanisms are reviewed and discussed.